Bioethical analysis in the use of non-human animals in the pharmaceutical industry - Linares Márquez, Pascual (2023)
In the last decade animal studies have increased, endorsed by ethics or bioethics committees in scientific research. However, this is not always clearly reflected in published articles relating to the pharmaceutical industry. This preliminary research aims to analyze the bioethical aspects that are established in scientific publications related to the pharmaceutical industry. Also, determine the commitment they establish with the principle of the "Three Rs" for the procurement of animal welfare and the establishment of better conditions for animals in experimentation. In the present study we find that animal experimentation to generate knowledge used by the pharmaceutical industry is applied to various human diseases. These studies omit bioethical data that clearly indicate that the animals used have welfare conditions since their intervention. We conclude that it is essential to give way to a better scientific application that does not demerit the conditions of animals intervened to generate medicines and that the Three Rs principle is applied very little in animal experimentation.